Chalcogenido‐Dimethylgallates and ‐Indates DMPyr2[Me2M(μ2−E)]2 (M=Ga, In; E=S, Se): Building Blocks for Higher and Lower Order Chalcogenidoindates. Issue 2 (10th February 2021) - Guschlbauer, Jannick; Vollgraff, Tobias; Finger, Lars H.; Harms, Klaus; Sundermeyer, Jörg
Abstract: Metalation of the anions in the ionic liquids DMPyr[SH] and DMPyr[SeH] (DMPyr=1, 1‐dimethylpyrrolidinium) by trimethylgallium and trimethylindium is investigated. The reaction proceeds via pre‐coordination of [EH] −, methane elimination and formation of an unprecedented series of chalcogenido metalates DMPyr2 [Me2 M( μ2 −E)]2 (M=Ga, In; E=S, Se). These show the presences of dinuclear dianions with four‐membered ring structures displaying highly nucleophilic bridging chalcogenide ligands in their crystallographically determined molecular structures. Some representative reactions of these building blocks with amphoteric electrophiles were studied: Addition of two equivalents of E(SiMe3 )2 (E=S, Se) to the indates DMPyr2 [Me2 In( μ 2 −S)]2 and DMPyr2 [Me2 In( μ2 −Se)]2 leads to a cleavage of the ring, E silylation and formation of mononuclear, monoanionic indates DMPyr[Me2 In(SSiMe3 )2 ], DMPyr[Me2 In(SeSiMe3 )2 ], and even a mixed sulfido‐selenido dimethylindate DMPyr[Me2 In(SSiMe3 )(SeSiMe3 )]. Reaction of DMPyr2 [Me2 In(μ2 −S)]2 with two equivalents of Lewis acid Me3 In leads to charge delocalization, ring expansion and formation of six‐membered ring DMPyr3 [Me2 In( μ 2 −S−InMe3 )]3 . The latter is a key intermediate in the formation of dianionic sulfidoindate DMPyr2 [(Me2 In)6 ( μ 3 −S)4 ] displaying an unusual inverse heteroadamantane cage structure with four capping sulfido ligands. Abstract : Thermodynamics in action ! Condensation of Me3 Ga and Me3 In with anions [EH] − (E=S, Se) to four‐membered rings, their cleavage or expansion and condensation to a cluster with inverse adamantane structure is driven by methane elimination, charge delocalization and dissociation.